2021
DOI: 10.1186/s13018-021-02536-w
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic analysis of Herbert screw fixation for capitellar fractures via the anterior approach in adolescent patients

Abstract: Objective The aim of this study is to analyze the efficacy of open reduction and Herbert screw fixation for coronal fractures of the capitellum via the anterior approach in adolescents. Methods We retrospectively analyzed the clinical and imaging data of 15 adolescents with capitellar fractures who were admitted to our hospital from May 2014 to May 2019. The fracture was reduced through the cubital crease incision via the anterior approach and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…We carried out a narrative review of the pediatric literature for capitellar shear fractures (shown in Table 1 ). Most of the literature consists of case reports ( 5 8 , 13 , 16 , 17 , 20 23 , 25 27 , 29 31 , 33 , 38 ), followed by a smaller number of retrospective case series ( 9 , 18 , 19 , 24 , 28 , 32 , 34 37 ). The retrieved literature showed a bimodal distribution of these fractures, with a first peak in childhood (<10 years) ( 7 , 17 , 20 , 31 ) and a second one, the most representative, in pre-adolescents and adolescents ( 5 9 , 13 , 16 , 18 , 19 , 21 25 , 27 30 , 32 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…We carried out a narrative review of the pediatric literature for capitellar shear fractures (shown in Table 1 ). Most of the literature consists of case reports ( 5 8 , 13 , 16 , 17 , 20 23 , 25 27 , 29 31 , 33 , 38 ), followed by a smaller number of retrospective case series ( 9 , 18 , 19 , 24 , 28 , 32 , 34 37 ). The retrieved literature showed a bimodal distribution of these fractures, with a first peak in childhood (<10 years) ( 7 , 17 , 20 , 31 ) and a second one, the most representative, in pre-adolescents and adolescents ( 5 9 , 13 , 16 , 18 , 19 , 21 25 , 27 30 , 32 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the aforementioned benefits, it is also used on other carpal bones fractures, 14 fractures in the elbow region 15,16 and patella fractures. 17 In 2013, the German company Syntellix introduced a magnesium alloy screw (CS model), declaring it fully self-resorbing and therefore a possible fix for the aforementioned complications.…”
Section: Introductionmentioning
confidence: 99%
“…Application of a Herbert screw is not limited to the scaphoid, though. Due to the aforementioned benefits, it is also used on other carpal bones fractures, 14 fractures in the elbow region 15,16 and patella fractures 17 …”
Section: Introductionmentioning
confidence: 99%